DA NECESSIDADE DE MORAR AO DESAFIO DE PERMANECER: COTIDIANO DOS MORADORES DOS CONJUNTOS HABITACIONAIS ARARA AZUL E JARDIM AEROPORTO - AQUIDAUANA-MS - Minéia Martins Cristaldo (2023)
Housing is a fundamental right protected by the law, and public housing policies serve as a means for people to access this essential asset. When we consider housing complexes designated for lower-income individuals who often have limited say in decision-making processes regarding the design and location of their homes, we start to realize the impact of these predetermined characteristics on their daily lives. In this analysis, our focus is on understanding the lived experiences of city dwellers, particularly those residing in social housing, such as the Arara Azul and Jardim Aeroporto housing complexes in Exposição, neighborhood of Aquidauana, Mato Grosso do Sul. Our goal is to unravel the spatial organization of these residents by delving into their day-to-day practices and uncovering the strategies they employ to interact with their living spaces. To achieve this, we have adopted a qualitative research approach, gathering rich and detailed information about their daily lives through interviews and conversations with the residents themselves. Additionally, we have conducted field observations and captured photographic records, immersing ourselves in their environment. Throughout our research, we have discovered that despite recognizing structural issues at both the neighborhood and housing levels, the residents expressed a sense of satisfaction in being provided with housing. However, it is evident that they yearn for changes in the properties and local conditions. This desire for improvement sheds light on both the shortcomings of the state’s role and the strategies they employ to adapt or envision forms that align with their own unique meanings and needs. Key words: Social interest housing. Everyday practices. Housing public policies. Place. Aquidauana-MS.